New frontiers in e-Business and e-Government: Emerging opportunities and challenges - Alexis Barlow; Peter Duncan; Feng Li; Savvas Papagiannidis (International Journal of Business Science & Applied Management (IJBSAM), 2007)
This paper is intended to provide an overview of the key issues that emerged from the presentations and discussion of a successful workshop organised by the British Academy of Management (BAM) e-Business & e-Government Special Interest Group at Newcastle University Business School on 9-10 November 2006. In addition to introducing the three main papers and the research note, which are based on the keynote presentations but have been revised in light of the discussions and questions as well as reviewers' comments on early drafts of the papers, we also highlight some of the key questions the participants raised and debated as well as issues that emerged from the open discussions.
Keywords: 650; e-business; e-government; e-public services; new technologies